Changes in muscle architecture of Biceps Femoris induced by eccentric strength training with Nordic Hamstring Exercise - Alonso-Fernandez, D.; Docampo-Blanco, P.; Martinez-Fernandez, J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Eccentric strength training alters muscle architecture, but it is also an important factor for the prevention of hamstring injuries. The purpose was to determine the architectural adaptations of the biceps femoris long head (BFlh) after eccentric strength training with nordic hamstring exercise (NHE), followed by a subsequent detraining period. The participants in this intervention (n=23) completed a period of 13 weeks consisting of a first week of control and prior training, followed by 8 weeks of eccentric strength training with NHE, and concluding with a 4-week period of detraining. The architectural characteristics of the BFlh were measured at rest using two-dimensional ultrasound before (M1—week 1) and after (M2—week 9) the eccentric strength training, and at the end of the detraining period (M3—week 13). The muscle fascicle length significantly increased (t=-7.73, d=2.28, P<.001) in M2 compared to M1, as well as the muscle thickness (t=-5.23, d=1.54, P<.001), while the pennation angle presented a significant decrease (t=7.81, d=2.3, P<.001). The muscle fascicle length decreased significantly (t=6.07, d=1.79, P<.001) in M3 compared to M2, while the pennation angle showed a significant increase (t=-4.63, d=1.36, P<.001). The results provide evidence that NHE may cause alterations in the architectural conditions of the BFlh and may have practical implications for injury prevention and rehabilitation programs.